Buddhism and Thai educational system: historical perspectives - Srinok, Somchai; Wongsuwan, Niwes; Buppapan, Saiyroong; Widesbrommakun, Phra; Thongdee, Vitthaya; Ruangsan, Niraj (Linguistics and Culture Review, 2021)
In Thailand, Buddhism has played an important role in terms cultivating morality and ethics for people in the society. Later, it has become an important part of the educational system of the country. This paper has its aims to clarify some backgrounds of Buddhist studies in Thai educational system from the early period to the present day. First, it discusses (1) some of the Buddha’s principles of teaching first, and thereafter (2) importance of Buddhist studies in Thai society, (3) management of Buddhist Studies, and (4) History of Buddhist Studies in Thailand and (5) Buddhist Studies Curriculum will be discussed. The conclusion of this study reveals that training morality and ethics to youth is the key factor making Buddhist studies exist in the educational system of Thailand.